Conocimientos y prácticas frente al uso de métodos anticonceptivos en adolescentes de una comunidad indígena del municipio de Coyaima-Tolima. (2022)
Adolescence is between the ages of 13 and 17, characterized by physical, psychological and social changes. This is an important stage because adult behaviors are beginning to be experienced and discovered, such as sexual activity and the exploration of risky behaviors such as the use of psychoactive substances. According to figures from the National Demographic and Health Survey (ENDS) 2015, Colombia obtains the highest rate of teenage pregnancy in the last 20 years, according to the results of the survey since there is evidence of an increase in households: in 2010 they were 9.5%, and by 2015 they represent 11.2%. The objective of this research is to describe the knowledge and practices regarding the use of contraceptive methods of the indigenous community of Zaragoza-Tamarindo in the municipality of Coyaima-Tolima.